PENGEMBANGAN MASYARAKATLAPORAN HASIL OBSERVASI DAN WAWANCARADESA PULAU BETUNG KECAMATAN PEMAYUNG - Ani Muntama Budiarti; Elka Fadhia Agnesa; Eva Puspita; Firli Amalia Dewi; Naomi Sianipar; Serlina Amanda; Vivi Maisa Erdita (Journal of Dialogos, 2024)
Community development is a process undertaken by individuals, groups, or institutions to improve the quality of life and welfare of the community as a whole. In this research, observation can be done in various contexts, such as: Daily Activities, Observations of the daily activities of villagers, such as agricultural activities, work in the fields, trading in the local market, and household activities.Social Interactions, Observing interactions between villagers, such as communication in public places, community meetings, traditional ceremonies, and other social events. Economic Life - Observations of the economic patterns of the village community, including the dominant types of work, trading methods, and survival strategies. Culture and Tradition, Looking at local cultural practices, such as religious rituals, traditional ceremonies, arts, and traditional crafts that exist in the village.Social Structure, Understanding the social structure in rural communities, including value systems, social hierarchies, gender roles, and kinship systems. Through observations of villagers, researchers can gain deep insights into life and social dynamics in the village, which can be the basis for designing development programs, public policies, or further research on rural communities. The purpose of an interview is to gain deeper information, understanding, or perspective on a particular topic, subject, or phenomenon. Interviews can be conducted in a variety of contexts, be it in scientific research, journalism, job selection, surveys, or in counseling.